A rare case of rectal gastrointestinal stromal tumour: diagnosis and management - Bansod, Atish N.; Jadhav, Vaishnavpriya K.; Umalkar, Rohan K.; Wankhede, Abhijit M.; Kothari, Kathan M. (International Surgery Journal, 2022)
Gastrointestinal stromal tumours are frequently defined as KIT-(CD117) or PDGFRA-positive mesenchymal spindle cell tumors. Gastrointestinal stromal tumors most commonly occur in the stomach and small intestine, with up to 5% of GISTs occurring in the colon and rectum. We presented a case of distal rectal GIST diagnosed by colonoscopy, colonoscopy with biopsy, computed tomography. The patient underwent Abdominoperineal resection (APR) and was confirmed on histopathology to have rectal GIST with tumor size more than 5 cm and mitotic rate more than 5/50 high power field (HPF). All GISTs are considered to have malignant potential, and, for that reason, all rectal GISTs should be considered for resection.